Reduced States Multilevel Space Time Coding - Al-Sanie, Nadia M.; Al-Ani, Muzhir Sh. (Nahrain University College of Engineering Journal, 2008)
There is an increasing demand for higher data rates and higher quality in wireless communications that has motivated the use of multiple antenna elements at both the transmitter and the receiver sides of a wireless link. Space-time coding (STC) deals with the design of good codes of multiple antennawireless systems.A new proposed orthogonal code is designed and presented in this paper as an improved design of delay diversity for multilevel space time coding with multiple inputs and multiple outputs. The code is based on using two signals transmitted at different rates in order to remove the problems thatappear from different types of fading due to multipath channel and to reduce intersymbol interference (ISI) between the symbols. The transmitter and the receiver are designed to encode and decode the proposed orthogonal code through the frequency selective and flat fading channels. Time invariant rapidlyvarying fading channel is included ; that the path gains change for each symbol. The detection is non coherent STC that neither the receiver nor the transmitter knows the channel propagation coefficients. Quasi-static fading channel with coherent STC is also included, that only the receiver has knowledge of thechannel through training symbols is available at the beginning of each frame of the receiver. The method gives coding gain, diversity gain as well as the design of the proposed code for three or four transmitting antennas with low complexity.